Arterial hypertension and obstructive sleep apnoea syndrome: treatment resistance and the role of autonomic dysfunction - V. V. Rostorotskaya; I. A. Elgardt; A. P. Ivanov; N. S. Sdobnyakova (Кардиоваскулярная терапия и профилактика)
Aim. To study the role of obstructive sleep apnoea syndrome (OSAS) in the development of treatment resistance in patients with arterial hypertension (AH). To assess the effects of autonomic nervous system (ANS) dysfunction, as one of the potential pathophysiological mechanisms of inadequate blood pressure (BP) reduction in patients with AH and OSAS. Material and methods. The study included 365 ambulatory AH patients: 194 with OSAS and 161 with resistance to antihypertensive therapy after 6-15 months. The 24-hour BP monitoring (BPM) and 24-hour cardio-respiratory monitoring of electrocardiogram (ECG), with heart rate variability (HRV) analysis, were performed. Results. Among patients with AH and OSAS, most individuals had low antihypertensive therapy compliance. All parameters of 24-hour BPM in this group were lower than in OSAS-free hypertensives, and this difference was more pronounced in patients with lower treatment compliance, particularly for pulse BP and HR. HRV parameters correlated with apnoea-hypopnoea index (AHI) and BP levels during 24-hour BPM. However, in multivariate analyses, these correlations were observed only for HRV parameters and AHI. Conclusion. In AH patients, OSAS aggravates the clinical course of the disease. ANS dysfunction could be one of the mechanisms underlying the development of antihypertensive treatment resistance.